Adolescent online victimization: a test of routine activities theory - Marcum, Catherine Davis (Criminal justice recent scholarship, 2009)
Introduction -- Adolescents and the age of the internet -- The prevalence of routine activities theory -- Investigating adolescent online victimization and formation of relationships with online contacts -- Univariate and bivariate results -- Uncovering potential factors of online victimization -- Applying the findings to the future